Determination of commercially valuable characteristics of plant varieties for energetic use during the state examination - В. В. Баликіна (Plant Varieties Studying and Protection)
The analysis of commercially valuable indices of plant varieties for energetic use was carried out and the necessity to determine energetic indices during the state scientific-and-technical examination is substantiated. In order to explain the requirements for registration of new varieties of energy crops concerning the defi nition of indices of ability for distribution, the collection of species and hybrid forms of willow was used. Factors that prove the economic and environmental advantages of energy willow cultivation for biofuel are specifi ed.